Analysis of risk factors for severe COVID-19 - Gruzieva, T.S.; Antonyuk, O.Ya. (KIDNEYS, 2023)
Global aging has accompanied the worldwide increase in average life expectancy over the past century. The coronavirus disease (COVID-19) pandemic has increased morbidity among all groups of the population, but it poses a particular threat to people of older age groups. Multiple concomitant pathologies form an unfavorable background for the course of COVID-19. It was found that the level of in-hospital mortality in the care of older age groups was high, including in countries with high-income levels and expenditures on health care. We have identified predictors of the severe course of COVID-19. In our opinion, such predictors should be considered when identifying risk groups and applying anticipatory strategies to them, in particular, timely hospitalization, the administration of antiviral therapy, and treatment of concomitant pathology (chronic kidney disease, hypertension, diabetes mellitus, etc.). The question of testing elderly patients for the presence of SARS-CoV-2 is especially relevant when weakness increases, the state of consciousness worsens, and/or dyspnea appears or worsens. Postponement of hospitalization can negatively affect the results of treatment. Thus, interleukin-6, C-reactive protein, the absolute level of lymphocytes, albumin, and ferritin can be used when evaluating the criteria for hospitalization in this group of patients. Interleukin-6 and C-reactive protein are positively associated with body mass index. The excess of adipose tissue is considered an independent predictor of severe COVID-19 and, unlike age, can be modified. We suggested that a hospital mortality risk calculator based on the personalized lethality risk index on admission should be used in practice. Adequate therapy of concomitant pathology is also important in the prevention of COVID-19 complications. Protection of susceptible groups at high risk of severe COVID-19 has strategic importance in preventing high mortality rates in population regardless of age.